Composite Materials Based on UPE Resin and Coffee Husks - Huynh, Nguyen Anh Tuan; Ly, Tan Nhiem; Dao, Minh Khanh (Journal of Technical Education Science, 2022)
In this work, two series of composite materials based on unsaturated polyester (UPE) resin and coffee husk powder were fabricated by a hot pressing method using methyl ethyl ketone peroxide (MEKP) as an initiator. The gel time of UPE resin is 32 ± 2 min with 0.5 wt % of MEKP was determined according to ASTM D2471. The differential scanning calorimetry (DSC) reveals that the curing process should be post-cured. The composite panels were fabricated with the size of 17x17x4 mm. With a bulk density of 1.35 g/cm3, two series of the composite material with two types of coffee husk sizes in the range of 0.150-0.315 mm (CH1) and 0.315-0.630 mm (CH2) were investigated. In each series, the coffee bean husk content varies by 45, 50, 55, 60, 65, and 70 wt %, respectively. The obtained composite materials were evaluated for mechanical properties such as flexural and tensile strength according to ASTM D790 and D638, respectively. The results show that the mechanical properties at the reinforcement content of 50% are the best with the flexural strength, flexural modulus, tensile strength and tensile modulus of the CH1 are 8.5, 616.0, 3.9, and 999.8 MPa, respectively. Meanwhile, they are18.7 MPa, 1888.5 MPa, 8.6 MPa, 8.6 MPa, and 1889.0 MPa, respectively for the CH2.